2022
DOI: 10.1017/s0007114522001763
|View full text |Cite
|
Sign up to set email alerts
|

Salinity levels affect the lysine nutrient requirements and nutrient metabolism of juvenile genetically improved farmed tilapia (Oreochromis niloticus)

Abstract: This 62-day research aimed to evaluate the effects of dietary lysine levels (DLLs) and salinity on growth performance and nutrition metabolism of genetically improved farmed tilapia (GIFT) juveniles (Oreochromis niloticus). Six diets with lysine supplementation (1.34, 1.70, 2.03, 2.41, 2.72 and 3.04% of dry matter) were formulated under different cultured salinities in a two-factorial design. The results indicated that supplemental lysine improved the SGR and WG and decreased the FCR. Meanwhile, the fish had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…The dietary amino acid composition in this study showed that lysine and methionine decreased as the ratio of dietary FM replacement by NGCP increased. It has been reported that the levels of dietary arginine [51] and lysine [52] affect the expression of the target of rapamycin (TOR) pathway, which is believed to respond to nutritional status in fish, leading to protein synthesis and growth [53]. The eIF4E-binding protein and ribosomal protein S6 kinase 1 are downstream effectors in the TOR pathway that regulate mTOR activity in an antagonistic manner [54].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary amino acid composition in this study showed that lysine and methionine decreased as the ratio of dietary FM replacement by NGCP increased. It has been reported that the levels of dietary arginine [51] and lysine [52] affect the expression of the target of rapamycin (TOR) pathway, which is believed to respond to nutritional status in fish, leading to protein synthesis and growth [53]. The eIF4E-binding protein and ribosomal protein S6 kinase 1 are downstream effectors in the TOR pathway that regulate mTOR activity in an antagonistic manner [54].…”
Section: Discussionmentioning
confidence: 99%